(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Internal haemorrhoid can be correlate with Abhyantar Gudarsha. The symptoms of Gudarsha are ankura in guda vali region along with pain in anal region and raktasrava through anal opening and kosthabaddhata and it has been included in Ashtamahagada. Sushruta described various types of treatment modalities in the management of Gudarsha such as Bheshaja, Ksharkarma, Agnikarma and Shastrakarma. Kshar chikitsa is effective second line of treatment for Gudarsha.